A Neutral Effect of Metformin Treatment on Macroprolactin Content in Women with Macroprolactinemia - Krysiak, R.; Szkróbka, W.; Okopień, B. (Experimental and Clinical Endocrinology & Diabetes, 2017)
Background: Metformin decreases serum levels of monomeric prolactin. No previous study has investigated the effect of metformin on macroprolactin content in patients with macroprolactinemia.Methods: We studied three age-, sex- and weight-matched groups of patients: 15 women with monomeric prolactin, 12 women with macroprolactin, as well as 15 women with normal prolactin levels. Because of coexisting 2 diabetes or prediabetes all patients were treated with metformin (1.7–3 g daily). Plasma lipids, glucose homeostasis markers, as well as serum levels of prolactin and macroprolactin were assessed at baseline and after 4 months of metformin treatment.Results: As expected, metformin reduced plasma glucose and triglycerides, as well as improved insulin sensitivity in all treatment groups. Moreover, the drug reduced post-polyethylene glycol prolactin levels and tended to reduce pre-polyethylene glycol prolactin levels in women with monomeric prolactin but not in women with macroprolactinemia and women with normal prolactin levels.Conclusion: The obtained results indicate that metformin has a negligible effect on macroprolactin levels.
Keywords: hyperprolactinemia; macroprolactin; monomeric prolactin; insulin resistance